An Investigation into the Supply Chain for Frozen Peas in Austria - Moussa, Tarek (2006)
Supply chain management has become increasingly important for companies in modern-day competitive markets. Competition in modern markets does not involve individual companies but entire supply networks. The performance of multi-national companies is greatly dependent on the efficiency and reliability of their suppliers and logistics providers. Supply chain management in the food industry has become an essential task due to the unique characteristics of this sector. Rapid deterioration of fresh foods and the need to maintain controlled conditions for frozen foods has important implications for supply chain efficiency. Failure to meet the logistical requirements for supply chains in the food sector can result in severe damage to physical products and brand reputations. This investigation analyses the supply chain of the leading frozen food supplier to the Austrian market. The market for frozen foods is experiencing rapid growth due to the convenience of frozen goods in modern-day lifestyles. The analysis focuses on frozen peas and investigates the flow of goods and information from farming to the display of finished products at the retailer. The aim of this study is to identify inefficiencies and all forms of supply chain waste that may exist in processes and activities. Once sources of waste have been located and quantified, the impact on products, companies and consumers is assessed and evaluated. In order to perform the analysis, data regarding the duration and cost of supply chain activities was collected through interviews with relevant stakeholders as well as through direct observations of supply chain operations. The analysis of the gathered data indicates that the supply chain for frozen peas contains several sources of operational waste such as lengthy transportation processes, extensive storage of excess inventory at several locations and improper material handling activities leading to quality deterioration of finished goods. These sources of supply chain waste can be traced to operational inefficiencies however, the lack of collaboration and integration of supply chain activities proved to play a significant role. An insight into the relationships between supply chain members revealed a lack of information-sharing, the absence of institutional trust and an overall fragmented sequence of processes. In order to successfully implement supply chain improvements, integration of supply chain processes as well as long-term collaboration between supply chain partners is of utmost importance. Once the supply chain operates as a single entity, operational improvements can be developed and implemented to increase efficiency and eliminate waste from processes and activities.